2004
DOI: 10.1002/elps.200406035
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate precision study on a capillary electrophoretic method for chlortetracycline

Abstract: We describe an intermediate precision study on a capillary electrophoretic (CE) method for chlortetracycline. It is shown how in one setup the influence of the factors time, analyst, and equipment on the precision can be investigated. As different types of CE equipments were included, the transferability of the method could be examined. Both the qualitative and quantitative aspect of the method were investigated. It was shown that small adaptations in method conditions can have a large influence on the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…It can be observed that the between-injection variances, s 2 i , contribute to the overall variability at all concentration levels. These results are similar to those observed in the intermediate precision study on the same type of equipment as well as in other intermediate precision studies [13]. The between-day variances, s 2 day , are small at all concentration levels.…”
Section: Intermediate Precision Study On Different Types Of Equipmentsupporting
confidence: 92%
See 2 more Smart Citations
“…It can be observed that the between-injection variances, s 2 i , contribute to the overall variability at all concentration levels. These results are similar to those observed in the intermediate precision study on the same type of equipment as well as in other intermediate precision studies [13]. The between-day variances, s 2 day , are small at all concentration levels.…”
Section: Intermediate Precision Study On Different Types Of Equipmentsupporting
confidence: 92%
“…This is consistent with the results of the study previously described by Dehouck et al [13]. The between-day variances, s 2 day , are in two cases negative and set equal to zero.…”
Section: Intermediate Precision Study On the Same Type Of Equipmentsupporting
confidence: 92%
See 1 more Smart Citation
“…[8]. The use of internal standards has been proposed to circumvent this problem [7,14]. Other issues arising in CE instrumentation, which call for data preprocessing, are baseline and time shifts between runs [15].…”
Section: Introductionmentioning
confidence: 99%
“…The highly efficient CE technique usually does not need extensive sample pre-treatment, enabling the separation of a variety of analytes within a short time. Despite its advantages, the difficulty in transferring the analytical method to other equipment is one of the problems encountered in CE [16,17]. This is due to the different technologies manufacturers use in their systems.…”
Section: Introductionmentioning
confidence: 99%